(untitled) (Research, Society and Development, 2020)
This article is about the “State of the Art” on the National Common Curricular Base - BNCC, with a qualitative approach classified as exploratory bibliography. The objective was to carry out the survey and analysis of the dissertations and theses defended in the period 2018 -2019, available at the Brazilian Digital Library of Theses and Dissertations - BDTD and answer the following questions: How many academic researches on BNCC are presented after the approval of said document in Brazil cataloged in the Brazilian Digital Library of Theses and Dissertations? How do these researches relate? How do the objectives of these researches converge? What are the contributions of these researches to the understanding of the theme? The chronological cut considered the publications from January 2018, considering that BNCC was approved by the Ministry of Education - MEC in December 2017. 14 publications were identified and, after the survey and analysis of these works, it was possible to conclude that some sought to reflect on the BNCC in the context of some specific areas of knowledge and in general discussed the guidelines for implementation in the school curriculum. Due to the diversity of research and interest in the results of the studies carried out through the referred research, we catalog and analyze these academic productions, as well as the contributions that these research bring to researchers who are interested in the subject, since this article shows what has to be done. most current in academic research on BNCC, in addition it will allow us to understand this theme starting with what has already been produced.